Impact of meridional wave-induced transport on sea surface temperature in mid -low latitude cold tongues - Wang, Yichen; Wu, Kejian; Li, Rui; Zhang, Wenqing; Dong, Xianghui; Lyu, Lingyun (Frontiers in Marine Science, 2025)
This study employs reanalysis data published by ECMWF to investigate the impact of ocean waves on cold tongues in the southern hemisphere. Based on the global sea surface temperature (SST) patterns, the scope of the cold tongue is defined in this paper. Compared to Ekman transport, wave transport dominates and plays a critical role in the cold tongue region. This study analyzes the characteristics of cold tongues across the three major ocean, with a primary focus on the Pacific cold tongue, which serves as the most representative region. Analysis of the relationship between meridional wave transport and SST in the southeastern Pacific cold tongue indicates a lagged negative correlation between abnormal SST and meridional wave-induced water transport from high latitudes. Specifically, negative SST anomalies in the Pacific cold tongue occur 3~4 months after a positive anomaly in northward cold-water transport from high latitudes. Meridional wave transport between 30°S and 38°S has a significant cooling effect on SST in the cold tongue region, with the strongest cooling observed along the northeastern coastline. Additionally, the combined effects of northward and westward water transport result in a distinct temperature gradient in the western cold tongue. These findings highlight the connection between wave-induced transport and the cold tongue, providing a novel perspective for exploring the causes of SST anomalies.